Palladium-Doped Tin Oxide Nanosensor for the Detection of the Air Pollutant Carbon Monoxide Gas - Jeyapaul Sam Jebakumar; Asokan Vimala Juliet (Sensors, 2020)
The exhaust gases from various sources cause air pollution, which is a leading contributor to the global disease burden. Hence, it has become vital to monitor and control the increasing pollutants coming out of the various sources into the environment. This paper has designed and developed a sensor material to determine the amount of carbon monoxide (CO), which is one of the major primary air pollutants produced by human activity. Nanoparticle-based sensors have several benefits in sensitivity and specificity over sensors made from traditional materials. In this study, tin oxide (SnO2), which has greater sensitivity to the target gas, is selected as the sensing material which selectively senses only CO. Tin oxide nanoparticles have been synthesized from stannous chloride dihydrate chemical compound by chemical precipitation method. Palladium, at the concentration of 0.1%, 0.2%, and 0.3% by weight, was added to tin oxide and the results were compared. Synthesized samples were characterized by X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM) techniques. XRD revealed the tetragonal structure of the SnO2 nanoparticles and FESEM analysis showed the size of the nanoparticles to be about 7–20 nm. Further, the real-time sensor testing was performed and the results proved that the tin oxide sensor, doped with 0.2% palladium, senses the CO gas more efficiently with greater sensitivity.